Modern Monetary Theory and the Post-Keynesians: the nature of their theoretical intersections in the literature. - Pahim, Rafael; Morrone, Henrique (Brazilian Keynesian Review, 2023)
The present paper aims to contribute to the post-Keynesian and Modern Monetary Theory (MMT) literature by bringing a Weberian methodological approach to the issue of MMT classification as a strand of post-Keynesian thought. In this sense, initially, the MMT and post-Keynesian theoretical cores are identified and elaborated by a literature review. Then both cores are compared. The working hypothesis is that MMT is a post-Keynesian strand, and research findings contribute to the validation of the hypothesis.